Variations in the relation between suspended sediment and solute delivery in glacial meltwaters, Maxwell Glacier, Yukon Territory. - Kruszynski, Glen A. (University of Ottawa (Canada), 1994)
The purpose of this thesis is to investigate the interactions between meltwaters and sedimentary material at the base of an alpine glacier which are indicated by intra- and interseasonal variations of discharge, solute and sediment outflow from the terminus. During the 1989 and 1990 ablation seasons, discharge, suspended sediment concentration and dissolved solids draining from Maxwell Glacier, St. Elias Mountains, Yukon Territory, were obtained at hourly intervals. The discharge time series of Maxwell Creek reveals that flow varies at a period of one to two weeks, at a diurnal level and over one to three hours. Over all three time scales, electrical conductivity is inversely proportional to discharge suggesting that during high during high diurnal flows, outwash water is derived primarily from surface melt while at low nocturnal discharge, water originates from subglacial and englacial stores. In spring, when supraglacial meltwater begins to access the subglacial drainage system the basal water pressure is raised. Large areas previously hydraulically isolated are integrated releasing stored basal sediment. During periods of increasing discharge in the early summer hydroglacial events resulting from gradual expansion and/or isolation of subglacial cavities, temporary blockage of subglacial conduits or from input from adjacent gravity deposits occur. As flow increases, conduit diameters increase and water gradually spreads out over the glacier bed as a diffuse network of linked cavities. Throughout the ablation season, different areas of the sole are integrated with flow. Towards the end of the ablation season, meltwater supply declines resulting in the reduction of flow in subglacial passageway and reduced sediment and solute supply. (Abstract shortened by UMI.)
Keywords: Physical Geography.